Optical Set up for Scanning System in Manufacturing Inspection. Issue 1 (1st March 2023) - Salah, Yosri Ben; Liu, Weiguo; Tian, Ailing; Sellami, Lamia; Hamida, Ahmed Ben
Abstract: Essentially, 3D scanning systems are fundamental in today's industry, since there is a necessity for the automation of the whole manufacturing process with the aim to achieve better results in terms of accuracy, quality, and manufacturing time. Indeed, experts move towards the integration of high-resolution sensors, and optical devices alongside software, which may offer several advantages for large manufacturing units. In this paper, a stereo vision system is demonstrated in detail while performing a scan. The developed model could be used to carry out several measurement experiments, and the measurement results are analyzed, which proved the correctness and feasibility of the method. Delivered results and outcomes are discussed.